A field study of the impact of a performance-based incentive plan - Banker, Rajiv D.; Lee, Seok-Young; Potter, Gordon (Journal of Accounting and Economics, 1996)
Much management accounting research focuses on design of incentive compensation contracts. A basic assumption in these contracts is that performance-based incentives improve employee performance. This paper reports on a field test of the multi-period incentive effects of a performance-based compensation plan on the sales of a retail establishment. Analysis of panel data for 15 retail outlets over 66 months indicates a sales increase when the plan is implemented, an effect that persists and increases over time. Sales gains are significantly lower in the peak selling season when more temporary workers are employed.